2020
DOI: 10.1111/arcm.12635
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study comparing the effects of thinning processes on the cross‐sectional morphologies of Early and Late Acheulian handaxes

Abstract: The refinement of handaxes, defined as increasing planview symmetry and profile thinness, has been used to distinguish Early and Late Acheulian assemblages. However, recent studies have found that this is not a ubiquitous trend throughout the Acheulian industry. Yet, research suggests that Late Acheulian handaxes differ from earlier forms in the complexity and extent of thinning procedures. To test the discriminatory power of thinning in distinguishing Early and Late Acheulian handaxes, cross-sectional shapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For example, the handaxes from the Area 1 locality at Amanzi Springs (~400 ka; Herries et al, under review) (Fig. 1), have been described as uniquely large and unstandardized despite their affiliation to the Later Acheulian period (Caruana, 2021;Caruana and Herries, 2020;Deacon, 1970;Sharon, 2007). It has been suggested that these morphological features resulted from the obstruction of reduction processes caused by raw materials flaws and knapping mistakes (Caruana, 2021;Caruana and Herries, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the handaxes from the Area 1 locality at Amanzi Springs (~400 ka; Herries et al, under review) (Fig. 1), have been described as uniquely large and unstandardized despite their affiliation to the Later Acheulian period (Caruana, 2021;Caruana and Herries, 2020;Deacon, 1970;Sharon, 2007). It has been suggested that these morphological features resulted from the obstruction of reduction processes caused by raw materials flaws and knapping mistakes (Caruana, 2021;Caruana and Herries, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Delpiano, Gennai and Peresani 2021; García-Medrano et al 2020a;Kolobova et al 2020a;Li et al 2021;Shipton and White 2020) and R (e.g. Archer et al 2021;Caruana 2021;Gill et al 2021;Presnyakova et al 2018;Sholts et al 2017) suggests that existing tools can be successfully applied to different regions and artefact types.…”
Section: Discussionmentioning
confidence: 99%
“…Cobble reduction predominates LCT shaping processes in the AMS1 sample, which suggests that knappers were collecting raw material packages based on overall size (Caruana & Herries 2020). Tip and bases thicknesses were seemingly difficult to control for the AMS1 knappers, which corresponds with the fact that evidence of thinning is rare in the LCTs at this locality (Caruana 2021;Caruana & Herries 2020.…”
Section: Interpreting 'Rule-sets' From Allometric Relationshipsmentioning
confidence: 94%
“…Comparisons between early and later Acheulean assemblages have revealed that the later period is typified by a high degree of variation in both size and shape, and that planview symmetry is not correlated with chronology (Li et al 2018;Caruana 2020Caruana , 2021Caruana & Herries 2021). However, differences in shaping strategies are noted between early and later Acheulean handaxes, where the latter examples show an increase in thinning of tip regions (Caruana 2020(Caruana , 2021.…”
Section: Background Regional Trends or One Homogenous Entity?mentioning
confidence: 99%